A Comparison of Coherence Based Acoustic Source Identification Techniques - Bennett, Gareth (My University, 2005)
Four techniques of source identification are examined and the performance of each evaluated with experimental data. The procedures are all frequency domain methods and depend to some extent on the coherence function. The Coherent Output Spectrum (COS) technique, reported by Bendat and Halvorsen [1], requires a measure of at least one input and one output irrespective of the number of inputs. The Signal Enhancement( SE) technique, developed by Chung [2], requires three output measurements for the identification of a single unmeasured source. The Conditional Spectral Analysis (CSA) technique, proposed by Hsu and Ahuja [3], is a combination of these, where one of two inputs is monitored with three output measurements. The final technique considered is applicable to a system which contains any number of inputs. For this, no input measure is required and the number of output measurements is a function of the number of inputs, as reported by Minami and Ahuja [4]. A series of tests have been conducted to examine the efficacy of each of the procedures for specific applications.
12th International Congress on Sound and Vibration (ICSV12)
PUBLISHED
Lisbon, Portugal
Keywords: Smart & Sustainable Planet